2012
DOI: 10.1186/ar3861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating joint-space narrowing and cartilage loss in rheumatoid arthritis by using MRI

Abstract: IntroductionMagnetic resonance imaging (MRI) has been shown to be superior to radiography (XR) for assessing synovitis, osteitis, and bone erosion in rheumatoid arthritis (RA), particularly in clinical trials. However, relatively little has been reported on the ability of MRI to evaluate articular cartilage loss, or joint-space narrowing (JSN), in the hands and wrists. In a previous study, we adapted the nine-point Genant-modified Sharp XR-JSN score for use with MRI (MRI-JSN). In this study, we compare MRI-JSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…Moreover, the IBJS was also highly correlated with CT suggesting this instrument potentially being a very good surrogate for cartilage changes in RA. These data extend recent observations by Peterfy and colleagues showing that conventional 1.5 T MRI has high specificity and accuracy in depicting joint space narrowing when compared with conventional radiography 21. Similar results were also shown by the group of McQueen assessing the wrist joints of patients with RA22 and by the OMERACT MRI Task Force 23.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the IBJS was also highly correlated with CT suggesting this instrument potentially being a very good surrogate for cartilage changes in RA. These data extend recent observations by Peterfy and colleagues showing that conventional 1.5 T MRI has high specificity and accuracy in depicting joint space narrowing when compared with conventional radiography 21. Similar results were also shown by the group of McQueen assessing the wrist joints of patients with RA22 and by the OMERACT MRI Task Force 23.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Eckstein et al 3 investigated cartilage imaging using MRI volume segmentation at the knee in women with osteoarthritis, and concluded that the technology was sufficiently robust to be recommended for large-scale multicentre trials. Peterfy et al 11 recently reported a study of JSN at the hand and wrist in 47 RA patients involved in two multicentre biologicals trials examining baseline MRI scans and radiographs. Using plain radiography as a gold standard, they found the sensitivity of MRI for JSN to be 0.94, specificity 0.91 and accuracy 0.91.…”
Section: Discussionmentioning
confidence: 99%
“…The ASSET Study24 showed suppression of bone erosion progression with abatacept+MTX in only 16 weeks, and both SCORE (rituximab)25 and GO-BEFORE (golimumab)26 showed suppression of bone erosion at 12 and 24 weeks, with statistical significance being reached in GO-BEFORE at 12 weeks. SCORE also showed suppression of cartilage loss using a nine-point MRI score8 at 24 weeks (cartilage loss was not evaluated at 12 weeks). In addition, all eight RCTs in table 1 showed suppression of synovitis and osteitis within 12 weeks.…”
mentioning
confidence: 99%